Chronic Proinflammatory Signaling Accelerates the Rate of Degeneration in a Spontaneous Polygenic Model of Inherited Retinal Dystrophy - Hollingsworth, T. J.; Wang, Xiangdi; White, William A.; Simpson, Raven N.; Jablonski, Monica M. (Frontiers in Pharmacology, 2022)
Collectively, retinal neurodegenerative diseases are comprised of numerous subtypes of disorders which result in loss of a varying cell types in the retina. These diseases can range from glaucoma, which results in retinal ganglion cell death, to age-related macular degeneration and retinitis pigmentosa, which result in cell death of the retinal pigment epithelium, photoreceptors, or both. Regardless of the disease, it’s been recently found that increased release of proinflammatory cytokines and proliferation of active microglia result in a remarkably proinflammatory microenvironment that assists in the pathogenesis of the disease; however, many of the details of these inflammatory events have yet to be elucidated. In an ongoing study, we have used systems genetics to identify possible models of spontaneous polygenic age-related macular degeneration by mining the BXD family of mice using single nucleotide polymorphism analyses of known genes associated with the human retinal disease. One BXD strain (BXD32) was removed from the study as the rate of degeneration observed in these animals was markedly increased with a resultant loss of most all photoreceptors by 6 months of age. Using functional and anatomical exams including optokinetic nystamography, funduscopy, fluorescein angiography, and optical coherence tomography, along with immunohistochemical analyses, we show that the BXD32 mouse strain exhibits a severe neurodegenerative phenotype accompanied by adverse effects on the retinal vasculature. We also expose the concurrent establishment of a chronic proinflammatory microenvironment including the TNFa secretion and activation of the NF-kB and JAK/STAT pathways with an associated increase in activated macrophages and phagoptosis. We conclude that the induced neuronal death and proinflammatory pathways work synergistically in the disease pathogenesis to enhance the rate of degeneration in this spontaneous polygenic model of inherited retinal dystrophy.